2011
DOI: 10.1080/09500839.2011.573813
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanical measurements of fracture toughness of bismuth embrittled copper grain boundaries

Abstract: Measuring the fracture properties of single grain boundaries has until now required macroscopic bi-crystals which are expensive and not always available. We describe a method for fracture testing using microcantilevers, manufactured using focussed ion beam machining and tested using a nanoindenter. We have used the method to measure the fracture toughness of selected grain boundaries in bismuth-embrittled copper. This technique is applicable to grain boundaries in other brittle polycrystalline samples for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…13 Recent work by Jaya et al 16 has shown that this microcantilever method produces fracture toughness values in silicon, which are in good agreement with fracture toughness values measured by other microscale means such as pillar splitting or double-edge-clamped beams as well as experimentally measured bulk fracture toughness values. Although micropillars have been tested to failure by compression in a range of brittle materials, 17,18 this does not allow the fracture toughness to be measured.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…13 Recent work by Jaya et al 16 has shown that this microcantilever method produces fracture toughness values in silicon, which are in good agreement with fracture toughness values measured by other microscale means such as pillar splitting or double-edge-clamped beams as well as experimentally measured bulk fracture toughness values. Although micropillars have been tested to failure by compression in a range of brittle materials, 17,18 this does not allow the fracture toughness to be measured.…”
Section: Introductionsupporting
confidence: 59%
“…Second, bend samples can be notched-either by FIB machining 13 or by other means such as using a sharp prenotch, 14 which allows the measurement of fracture toughness of either bulk materials 8,10,14 or of individual microstructural features such as phase interfaces 15 or grain boundaries. 13 Recent work by Jaya et al 16 has shown that this microcantilever method produces fracture toughness values in silicon, which are in good agreement with fracture toughness values measured by other microscale means such as pillar splitting or double-edge-clamped beams as well as experimentally measured bulk fracture toughness values.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ion beam machining has been used to manufacture small cantilevers (H25µm x 4µm x 6µm) ( Fig. 10), which are then deflected to fracture using a nano-indenter, to measure the fracture 13 toughness of single grain boundaries [25][26][27]. Initial results (Fig.…”
Section: Ductilisationmentioning
confidence: 99%
“…Single GBs in real alloys were also generated and monitored by using cantilevers manufactured by focused ion beam (FIB) and tested by nanoindentation, which was expected to provide a more accurate method of measuring the crack growth and investigate the dependence of SCC resistance of the single GB on GB character and composition [19][20][21][22]. However, it is difficult to manufacture a specific single GB with respect to the random orientation of neighboring grains and also to accurately measure the stress and strain distribution near the GB.…”
Section: Introductionmentioning
confidence: 99%